Tablet computers for recording tuberculosis data at a community health centre in King Sabata Dalindyebo Local Municipality, Eastern Cape: a proof of concept report - Don O'Mahony; Graham Wright (South African Family Practice)
Background: Data at primary healthcare (PHC) clinics are handwritten in registers by nurses for submission to the District Health Information System (DHIS). Compared to pen and paper, data capture, using handheld computers, has fewer errors, is more efficient and is readily accepted by users. This study describes the process of developing a tablet computer programme to capture data, and explores nurses’ experiences of using tablets at a community health centre.